KOMPOSISI DAN KEANEKARAGAMAN HASIL TANGKAPAN JARING INSANG HANYUT (SURFACE GILLNET) DI PERAIRAN TANJUNG LUAR KABUPATEN LOMBOK TIMUR - lalu samsul rizal; Nehemia Wolla Gole (Universitas Muhammadiyah Gresik, 2024)
Gill net is a fishing device made of 4 rectangular nets equipped with a weight on the lower line and a buoy on the upper line. When operated, several sheets of nets are combined into one and positioned to block the current to block the direction of the fish's swimming movement. The purpose of this study is to determine the composition and diversity of gill net catches operated in Tanjung Luar waters, to find out the specifications of gill net fishing gear operated in Tanjung Luar waters, and to find out how to operate gill net fishing gear operated in Tanjung Luar waters. Analysis of gill net catch composition data by comparing the number of primary and secondary catches using equations (Salim and Kelen, 2017; Nofrizal et al., 2018; Mauliddin et al., 2022) and analysis of the diversity of gill net catches using the diversity index formula H′ = Pi ln Pi. The percentage of the composition of the gill net catch is the main catch (HTU) of 96.56% with a total weight of 350.4 kg consisting of selar bentong, mackerel, gray flying fish, and lemuru. Meanwhile, the bycatch (HTS) was 3.44% with a total weight of 12.5 kg consisting of petami fish and squid. The diversity index value is 1,377, which indicates that the level of diversity is moderate by the criteria of 1 < H' < 3.